(3MOjK CHj YHO Gddg GdMSjf Hf jMji Hf YjGT Yf GdMSf Hf YQaIs - (3YHjO Gddg Hf eMeO Hf CMeO Hf CHj eSde GdaQVj, CHhCMeOs ((3eMeO Hf eci Hf CHj GdKfGA GdOfjSQi s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdaGQbi MOKfG CHh YHO Gddg YjGT GdbWGf bQGAI Ydjg s
(3BNQgG (B:s
(3abGdJ bQjT hGdCfUGQ hPcQ GdMOjK gPG LejY eG cGf YfO CHj CMeO Yf CHj YHO Gddg Hf YjGT s
(3HCUdgG Gdefbhd efg SeGYGJ cKjQI HYVgG SfI (B581s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN SdjeGf Hf UGdM Hf MeO Hf HSGe dGNGUI HYfjRIs
Keywords: (3GdMOjK h GdeUWdMs